State ownership, cross-border acquisition, and risk-taking: Evidence from China’s banking industry - Zhu, Wenyu; Yang, Jiawen (Journal of Banking & Finance, 2016)
Does state ownership breed risk-taking behavior in commercial banks? This paper examines this issue using a panel of Chinese banks. We find that state-ownership is in general associated with higher risks. In addition, we find that banks controlled by the central government have the highest credit risk, while those owned by local governments have the lowest capital adequacy ratio and liquidity ratio. By compiling a complete list of cross-border acquisitions in China’s banking sector, we investigate the impact of foreign acquisition on state-owned banks’ risk-taking using differences-in-differences and matching estimators. We find that foreign acquisition has a reducing effect on state-owned banks’ risk-taking and this effect is particularly significant for banks that are controlled by central or local government. We also find that this risk-reducing effect depends on the percentage of foreign ownership, the local business involvement of the foreign investors, and the number of foreign members on the banks’ boards of directors.